Enhancing plant diversity in agricultural landscapes promotes both rare bees and dominant crop‐pollinating bees through complementary increase in key floral resources. Issue 6 (10th April 2017) - Sutter, Louis; Jeanneret, Philippe; Bartual, Agustín M.; Bocci, Gionata; Albrecht, Matthias
Summary: Enhancing key floral resources is essential to effectively mitigate the loss of pollinator diversity and associated provisioning of pollination functions in agro‐ecosystems. However, effective floral provisioning measures may diverge among different pollinator conservation targets, such as the conservation of rare species or the promotion of economically important crop pollinators. We examined to what extent such diverging conservation goals could be reconciled. We analysed plant–bee visitation networks of 64 herbaceous semi‐natural habitats representing a gradient of plant species richness to identify key resource plants of the three distinct conservation target groups: rare bees (of conservation concern), dominant wild crop‐pollinating bees and managed crop‐pollinating bees (i.e. honeybees). Considering overall flower visitation, rare bees tended to visit nested subsets of plant species that were also visited by crop pollinators (46% and 77% nestedness in the dissimilarity between rare bees and wild crop pollinators or managed honeybees respectively). However, the set of preferred plant species, henceforth 'key plant species' (i.e. those species disproportionately more visited than expected according to their floral abundance) was considerably more distinct and less nested among bee target groups. Flower visits of all bee target groups increased with plant species richness at a similar rate. Importantly, our analyses revealed that an exponential increase in the flower abundance of the identified key plant species and complementarity in the bee visitation pattern across plant species ─ rather than total flower abundance ─ were the major drivers of these relationships. Synthesis and applications . We conclude that the multiple goals of preserving high bee diversity, conserving rare species and sustaining crop pollinators can be reconciled if key plant species of different target groups are simultaneously available. This availability is facilitated by a high floral resource complementarity in the plant community. The list of identified key resource plant species we provide here can help practitioners such as land managers and conservationists to better design and evaluate pollinator conservation and restoration measures according to their goals. Our findings highlight the importance of identifying and promoting such plant species for pollinator conservation in agricultural landscapes. Abstract : We conclude that the multiple goals of preserving high bee diversity, conserving rare species and sustaining crop pollinators can be reconciled if key plant species of different target groups are simultaneously available. This availability is facilitated by a high floral resource complementarity in the plant community. The list of identified key resource plant species we provide here can help practitioners such as land managers and conservationists to better design and evaluate pollinator conservation and restoration measures according to their goals. Our findings highlight the importance of identifying and promoting such plant species for pollinator conservation in agricultural landscapes.